Determining the Relationship between Corporate Social Responsibility and Company Profitability in Zimbabwe: A Case of a Listed Telecommunication Company - Banele Dlamini (Current Aspects in Business, Economics and Finance Vol. 4, 2022)
The purpose of the study is to investigate and analyze the connection between corporate social responsibility (CRS) and Company profitability in Zimbabwe. The idea of sustainable development emphasises that organisations should place a priority on economic and business outcomes as well as pay attention to the environment, society, and community where they conduct business. CSR is seen as a crucial component of strategic planning. It might result in increased Company profitability. To examine the influence of CSR on profitability, the study used the Vector Auto Regression (VAR) model of regression analysis with Stata as the statistical instrument. Secondary data was gathered from yearly reports of a Zimbabwean Listed Private Limited firm, correlation and regression analysis were employed, and the hypothesis was evaluated. In Zimbabwe, the telecommunications industry plays a vital role in the success and ongoing viability of a corporate and it is at the forefront of the information age. For the period 2010 to 2015, the firm was the sole publicly traded mobile telecommunications operator in Zimbabwe, out of three under the Ministry of Information, Communication Technology, Postal and Courier Services (MICTPCS). As the regulatory agency, MICTPCS encourages mobile telecommunications businesses to incorporate CSR as a customer-oriented aspect into their business operations. According to the study’s conclusions, there is no causal association between Corporate Social Responsibility and profitability, and CSR has no meaningful impact on profitability [1-3]. Zimbabwe has no Corporate Social Responsibility policy; firms participate freely as a marketing tactic, and there is a need for a policy to be developed and enforced to ensure that entities operate ethically.